2021
DOI: 10.1186/s12913-021-06166-0
|View full text |Cite
|
Sign up to set email alerts
|

Cost analysis of pediatric intensive care: a low-middle income country perspective

Abstract: Background Globally, Pediatric Intensive Care Unit (PICU) admissions are amongst the most expensive. In low middle-income countries, out of pocket expenditure (OOP) constitutes a major portion of the total expenditure. This makes it important to gain insights into the cost of pediatric intensive care. We undertook this study to calculate the health system cost and out of pocket expenditure incurred per patient during PICU stay. Methods Prospective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Ariwala and colleagues reported an annual cost of treating child FBA cases of nearly $12.8 million (23). Additionally, the average cost of treating a patient in a PICU was estimated at approximately US$2100 in India (24). It's worth noting that treatment in the PICU is often more expensive, nearly four-fold, compared to treatment in a regular ward (24).…”
Section: Discussionmentioning
confidence: 99%
“…Ariwala and colleagues reported an annual cost of treating child FBA cases of nearly $12.8 million (23). Additionally, the average cost of treating a patient in a PICU was estimated at approximately US$2100 in India (24). It's worth noting that treatment in the PICU is often more expensive, nearly four-fold, compared to treatment in a regular ward (24).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric sepsis is an important cause of mortality in children admitted to the pediatric intensive care unit (PICU). It is increasing in incidence and increasing the mortality and costs in the health care system, making it a worldwide public health problem 12 . Despite its being a topic of main concern, there is still little data on global prevalence and mortality about it and even less epidemiologic information available 13 .…”
Section: Observationsmentioning
confidence: 99%
“…It is increasing in incidence and increasing the mortality and costs in the health care system, making it a worldwide public health problem. 12 Despite its being a topic of main concern, there is still little data on global prevalence and mortality about it and even less epidemiologic information available. 13 The different definitions of sepsis do not allow uniformity in records.…”
Section: Socioeconomic and Demographic Aspectsmentioning
confidence: 99%
“…This study examined multiple variables contributing to the LOS. Previous studies identified several factors that contribute to the LOS including patient age, severity of illness, presence of nosocomial infections, acute kidney injury, cardiorespiratory disease, post-cardiac intervention patients, and patients with cardiac arrest before admission (4)(5)(6)(7)(8)(9)(10)(11)(12)(13). Complications related to clinical conditions, such as drugdrug interactions and hospital-acquired infections (HAIs), are also associated with prolonged LOS (10,14).…”
Section: Introductionmentioning
confidence: 99%